Rekomendasi Promosi Kenaikan Jabatan Pada Pegawai Balai Penelitian Sembawa Provinsi Sumatera Selatan - Suryati Suryati (Program Studi Sistem Informasi, 2020)
Decision maker or official who has the authority as a decision maker in determining the position / position of his employee can make a decision to promote a promotion, of course, has criteria for assessing the credibility of the employee who will be upgraded according to the procedure for promotion. This assessment has several conditions / criteria that must be assessed and these criteria must apply to all employees. In the DSS system, to determine the assessment of the person who will be assessed, of course, must have assessment criteria that have become the standard of assessment and the value of the assessed criteria, so that the assessment can be carried out fairly, while an appraisal official does not feel any doubt about the decision made will be done The Simple Additive Weighting (SAW) method is in accordance with the decision-making process because it can determine the weight value for each assessment, with each criterion given a weighted value according to the interests of the organization / institution where the employee works, using the Simple Additive Weighting (SAW) method), the decision makers do not have any doubts in making a decision. So, the decisions received by employees can be done fairly and equitably because the assessment applies to all employees / employees in an organization / institution. In this case no one feels aggrieved, because in the decision maker in making a decision based on a method that is believed to be able to provide good and correct decision results. This weight value lies in its ability to make a more precise assessment because it is based on the performance appraisal and the weights that have been determined.Keywords: Criteria, Decision maker, Employee, Promotion, Recommendation